(untitled) (American Journal of Islam and Society, 2004)
This article is written in response to the favorable critical reception that V. S. Naipaul’s writings about the Muslim world have received in mainstream western culture. Since the publication of his travel narratives, Among the Believers and Beyond Belief, Naipaul has enjoyed a reputation as an authority on the Muslim world. The critical acclaim that he has received has been accompanied by official recognition, including a knighthood and the Nobel Prize for Literature. However, many critics beyond the periphery of mainstream western culture have voiced concerns about his hatred of Islam. In this article, I offer a revisionist reading of Naipaul’s most recent Islamic travel narrative, Beyond Belief, arguing that Islamophobia has been disturbingly misinterpreted as expertise. Focusing on three main literary themes – nineteenth-century literary conventions, the gothic genre, and neurosis – I expose this bigoted worldview and call for his status to be reconsidered.